2014
DOI: 10.1186/s12935-014-0079-7
|View full text |Cite
|
Sign up to set email alerts
|

HOXA11 gene is hypermethylation and aberrant expression in gastric cancer

Abstract: BackgroundAberrant DNA methylation is an acquired epigenetic alteration that serves as an alternative to genetic defects in the inactivation of tumor suppressor genes and other genes in diverse human cancers. Gastric carcinoma is one of the tumors with a high frequency of aberrant methylation in promoter region. Hence we investigated the promoter methylation status and expression level of HOXA11 gene which may involve in GC development.MethodsThirty-two surgical excised gastric cancer specimens, twelve paired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…The expression of HOXA11 was found unchanged in normal and malignant cervical cells (Lopez et al, 2006b). A report from Bai et al indicates that HOXA11 is regulated by methylation and that the expression of this gene decreases in gastric cancer; moreover, these authors observed that silencing of HOXA11 induced cell proliferation of tumor cells (Bai et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…The expression of HOXA11 was found unchanged in normal and malignant cervical cells (Lopez et al, 2006b). A report from Bai et al indicates that HOXA11 is regulated by methylation and that the expression of this gene decreases in gastric cancer; moreover, these authors observed that silencing of HOXA11 induced cell proliferation of tumor cells (Bai et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…A study by Bai et al (64) observed that the methylation frequencies of HOXA11 in gastric cancer tissues and adjacent cancer tissues were higher than those in normal gastric mucosa (P<0.05). Furthermore, HOXA11 expression was downregulated following hypermethylation of the promoter region (64); this suggests that HOXA11 may function as an important repressor in gastric cancer tumorigenesis, and aberrant promoter methylation may be the primary cause behind the loss or downregulation of HOXA11 expression, subsequently resulting in gastric cancer carcinogenesis.…”
Section: Hox Genes and Cancermentioning
confidence: 94%
“…A study by Bai et al (64) observed that the methylation frequencies of HOXA11 in gastric cancer tissues and adjacent cancer tissues were higher than those in normal gastric mucosa (P<0.05). Furthermore, HOXA11 expression was downregulated following hypermethylation of the promoter region (64); this suggests that HOXA11 may function as an important repressor in gastric cancer tumorigenesis, and aberrant promoter methylation may be the primary cause behind the loss or downregulation of HOXA11 expression, subsequently resulting in gastric cancer carcinogenesis. The study also observed that hypermethylation of HOXA11 was significantly associated with lymph node metastasis and Tumor-Node-Metastasis stage in gastric cancer, and in vitro experiments demonstrated that HOXA11 may control cell growth with its defect enhancing cell proliferation (64).…”
Section: Hox Genes and Cancermentioning
confidence: 94%
See 1 more Smart Citation
“…It was reported that HOTTIP may regulate the expression of HOX genes, including HOXA1, HOXA9, HOXA10, HOXA11 and HOXA13, in liver cancer and pancreatic cancer (15)(16)(17). In addition, numerous studies have reported that aberrant expression of HOXA genes was associated with a number of biological characteristics of gastric cancer (34)(35)(36)(37). HOTTIP may be critical in regulating HOXA genes in gastric cancer, but the underlying mechanism remains unknown and requires additional study.…”
Section: Discussionmentioning
confidence: 99%